ANALYSIS OF CREDIT SALES ACCOUNTING PROCEDURE FORWARDING COMPANY - Pramitasari, Dini Ayu; Hasanah, Anisaul; Mufidah, Imtiyaz Farras (International Journal of Business, Law, and Education, 2023)
This study aims to analyze and find out the accounting procedure for credit sales at PT. RTL EXPRESS. This research uses qualitative methods using a descriptive qualitative approach. The credit sales accounting information procedure at PT RTL EXPRESS is quite good. This is evidenced by the company has compiled an organizational structure in accordance with their respective duties and responsibilities, including sales functions, credit functions, warehouse functions, shipping functions, accounting and billing functions. Based on the results of the research conducted as already described, this study aims to determine the application of PT RTL EXPRESS credit sales accounting procedures, it can be concluded that accounting procedures at PT RTL EXPRESS have been running well where the company provides programs that can be used to facilitate operational activities. One of the companies in terms of credit sales. However, there are still things that are not right where there are dual functions, namely the sales function and the accounting function.